Minimizing the Trends of Plagiarism among Prospective Special Education Teachers: A Way Forward towards Academic Integrity - Kashif Iqbal; Samina Ashraf; Humaira Bano; Salim Razı (Sustainable Business and Society in Emerging Economies)
Purpose: Plagiarism is a real threat to academic integrity at higher education levels. This study seeks to minimize the trends of plagiarism among prospective special education teachers.